Pengaruh Analisis Standar Belanja, Standar Pelayanan Minimal dan Indikator Kinerja terhadap Penyusunan Anggaran Berbasis Kinerja (Studi Kasus Pada Satuan Kerja Perangkat Daerah Kota Pangkalpinang) - Wenni Anggita (UNSIKA (Universitas Singaperbangsa Karawang), 2017)
This study aims to determine how much influence from the standard variable expenditure analysis, minimum service standards and performance indicators against which performance-based budgeting in the city Pangkalpinang investigated. This research is a quantitative survey approach. Total sample of 72 people is obtained from a population of 84 people who were taken from 24 SKPD Pangkalpinang city. Using the census sample retrieval method. The independent variables consist of the standard analysis of expenditure (X1), minimum service standards (X2) and indicator linerja (X3) while the dependent variable is the performance-based budgeting (Y). Tests using the instrument validity and reliability testing. The method of data analysis using multiple linear regression with F test and T test. The results showed that the standard variable expenditure analysis no effect partially on performance-based budgeting. For variable minimum service standards and performance indicators affect both partially on performance-based budgeting. Overall the standard variable expenditure analysis, minimum service standards and performance indicators have a positive and significant impact on the performance-based budgeting.